THE ETIOLOGICAL STRUCTURE OF MASS DISEASES WITH YOUNG GASTRO AND RESPIRATORY SYNDROME - Nikolaj Zuev; Vladimir Bukhanov; Aleksandr Vezentsev; Pavel Sokolovsky; Aleksey Khmyrov; Bui Quang; E. Salashnaya; Mariya Mihaylyukova (Belgorod National Research University, 2016)
The study of the etiology and pathogenesis of diseases gastrointestinal and respiratory tract, the development of effective methods of these treatment and prevention are of great economic importance in ensuring the country's food animal population. Widespread gastrointestinal and respiratory diseases (25-76%) in large livestock farms due to the impact on the body of animals and birds of many technological-ray stress factors, reducing the natural resistance of the organism, pathogenic and opportunistic pathogenic microorganisms, both individually and in various associations. Etiology gastroenteritis and pneumonia animals studied complex, on the basis of epizootic, clinical, pathological data, bacteriological results, serology, hematology, immunobiochemical research methods. For detection of antibodies to pathogens of viral and chlamydial Institute infections using standard biofabrichnye antigens. Antimicrobial activity tilozinsoderzhaschih drugs against reference strains of mycoplasma, aholeplazm and field cultures of E. coli, Pasteurella and Staphylococcus aureus was investigated in liquid and solid culture media using an indicator 2,3,5 - triphenyltetrazolium chloride. Found, in the etiology of gastro-intestinal and respiratory diseases young farm animals participating Gram positive (Staphylococcus) and Gram negative (Escherichia, Salmonella, etc.) microorganisms, which usually stand in various combinations. The isolated microorganisms studyed degree of habituation to widely used in veterinary medicines practice (furazonalu, biovitu, sulgin, ampicillin, neomycin, streptomycin). Found that during several passages of them through the culture medium containing drugs (streptomycin, neomycin and ampicillin sulfates, tylosin tartrate, furazonal, Biovit, sulgin), microorganisms become resistant to them.